Assistive Technology: a Dynamic Tool to Deal with the Changing Needs of People with Disabilities - Méndez-Fernández, Héctor L. (Puerto Rico Health Sciences Journal, 2009)
Due to the accelerating rate of the industry’s constant innovations, more users become dependent on the most recent technology available on the market. Assistive technology is no exception, as the needs of people with disabilities are constantly changing. A retrospective transversal cohort study was designed in order to evaluate the needs of people with disabilities in relation to assistive technology, and how these needs change over time. This study compares the needs of people with disabilities over the last five years, based on the 952 participants’ personal experience in the assistive technology study carried out by Puerto Rico Assistive Technology Program (PRATP) from March 2003 to March 2007. Various statistical tests were carried out in order to determine if there is a significant difference between the reported assistive technology needs and the years of the study. Test results showed a significant statistical association between participants’ knowledge level of assistive technology and the years of the study. Similarly, it showed a significant difference between the priority work areas and the years of the study. Besides, statistical associations between sectors, types of disabilities, and work priorities were established in order to determine areas of need in accordance with consumers or service providers’ characteristics or particular interests.